Desarrollo de nuevos productos: consideraciones sobre la integración funcional. - Rodríguez Duarte, Antonio; Arias Aranda, Daniel; Minguela Rata, Beatriz (Cuadernos de Estudios Empresariales, 2000)
Fast changes in customers' needs and technological evolution, shorier pro duct life cycles, and intense international and domestie competition modify today's business environment. In this context, innovation, design or new product development becomes a critical and vital activity. Interdependency and informa tion sharing between marketing, R&D, and manufacturing are supposed to play a fundamental role. However, Ihis eross-functional co-operation is very difficult te reach because of differences among functions such as training, formation, cultu re and responsibilities. Conflicts in these areas are expected to appear concerning organisational goals, evaluation and reward procedures, broad or narrower pro duct lines, breakthrouglx new products, inventory invesimení, etc. Sn order to reach cross-functional integration, communication will be a essential issue. This paper reviews literature about new product developmcnt process activities foen sing on sequential versus overlapping approaches. A greater emphasis is inade on 165 Beatriz Minguela Rata, et al. Desarrollo de nuevos productos: consideraciones... Ibe latter due lo jIs adequacy lot organisations which develop new products quickly (id est, reducing development cycle time) and in a flexible way. Afterwards, we underlie the importance of cross-functional teams br new projects developmení. 1.